Journal Review of Capitalism in European Soccer - Juan Pradipta; Geffin Wartuny (Kantor Pelatihan Bahasa dan Budaya, Universitas Atma Jaya Yogyakarta. Gedung Santo Alfonsus, Jl. Mrican Baru No.28, Mrican, Caturtunggal, Kec. Depok, Kabupaten Sleman, Daerah Istimewa Yogyakarta 55281 Phone: (0274) 514319 Email: kpbb@uajy.ac.id, 2024)
In the past few decades, the European football industry has become a major source of mass entertainment as well as a vibrant platform for capitalism. This essay offers a critical analysis of the ways in which capitalism has influenced the development of European football. This article investigates the economic, social, and cultural ramifications of capital's domination in professional football through a theoretical analysis and case study methodology. The development of football teams into multinational corporations under the ownership of oligarchs and international investors is covered in this examination. The morals and principles that guide the sport are also impacted by these structural modifications, in addition to the clubs' financial operations. This review also looks at how capitalism affects football's diversity and cultural identity, as well as how it affects the balance of competition between clubs. This analysis focuses on the moral dilemmas that arose from capitalism's hegemony in European football, including matters of financial disparity, the commodification of sportsmen, and the displacement of local communities by corporate interests. This review provides a deeper understanding of the complexities of the relationship between European football and capitalism by summarizing critical viewpoints from a range of angles. It also highlights viable alternatives for maintaining the integrity of a sport that is cherished by millions of fans worldwide. Keywords: Football, industry, capitalism.